Looking at or through rose-tinted glasses? Imagery perspective and positive mood. - Holmes, E; Coughtrey, A; Connor, A (2008)
We can imagine looking at ourselves (observer perspective) or through our own eyes (field perspective). Cognitive and clinical theories suggest that compared to field perspective, observer perspective imagery reduces emotional intensity, for example, of trauma memories. Tests of causality are lacking and less is known about perspective and positive emotion. Using contrasting experimental manipulations, participants imagined 100 positive descriptions from either (1) a field perspective or (2) an observer perspective, or (3) thought about their verbal meaning. Affect was more positive after field than observer imagery and verbal conditions, with mood deterioration within the latter two. Findings are the first to demonstrate causality of imagery perspective on emotion. Further, the results demonstrate that imagining positive events from one's own perspective is critical to improving positive affect. Treatment implications include promoting field imagery to facilitate a more rose-tinted view of positive events.